Antibiotic use practices in semi-intensive production poultry systems in Laos - Phutthana, V. (National University of Laos, 2024)
In recent years, semi-intensified and intensified poultry production in Laos has become common and is expanding rapidly. This intensification trend favors the demanded use of antimicrobials for growth promotion, prophylaxis, and treatment. Numerous action areas to reduce antimicrobial resistance (AMR) and preserve the efficacy of existing drugs in the poultry value chain have been initiated under several global, regional, and national AMR plans. This study aimed to develop the evidence base on the drivers of antimicrobial use (AMU) among farmers in semi-intensive poultry production systems, so that key features of the production system can be captured to build understanding of the drivers of AMU by Laotian farmers. A cross-sectional survey, using a structured questionnaire, was conducted in poultry farms across districts in Vientiane, Bolikhamxay and Luangprabang provinces from February to March 2024. A total of 250 broiler farms were selected from the list of chicken farms which were provided by local veterinary and husbandry authorities. Amongst the farmers interviewed, 60% were female, who often oversaw raising chicken in the survey farms. Almost half of the farms (47.2%) gained some of their family income from broiler farming, while 5.6% of the respondents said chicken farming accounted for most or all of their family income. Only 8.5% of respondents reported that they have attended at least one training related to animal (chicken) husbandry or veterinary care. The studied farms which used fences partly or completely around the pen or farm area accounted for 47.6% and 29.3% of surveyed farms, respectively. Farms not using fences accounted for 23.1% of total farms. Most of the farms (92.5%) had no footbath at the farm gate or pens entrance. Seventy-one percent (71%) of farmers mentioned that they have used antibiotics for their chicken in the last production cycle. When asking about farmer’s perception on the main purpose of using antibiotics in poultry production, two third of respondents (76.1%) reported ‘to prevent the diseases.’ The average amount of money, which farmers spent on antibiotics in the last cycle was LAK 100,000 (~ USD 5, min-max: USD 0.35-40). Over the year, farmers use antibiotics most in June and July, followed by January and February. The months farmers used the least amount of antibiotics were March and April. About 18% of respondents revealed that they have mixed antibiotics in commercial feed either at starter or finisher stage. The common antibiotic types used were doxycycline and some farmers mixed tetracycline and erythromycin into feed. For treatment or metaphylaxis e.g. after vaccination of birds, farmers used doxycycline mixed in feed. Other antibiotics used for treatment included oxytetracycline.